Traditional food for mitigating food and nutritional security in Western India during harsh period - Meena, Nirmal Kumar; Meena, Vijay Singh; Choudhary, Kalpana; Sharma, Ankita (Indian Farming, 2021)
Under Indian condition uses ofthese traditional foods could playcrucial role in overcoming food andnutritional security. Processing andmarketing of ethnic foods have greatscope and area under this changingscenario. As a result of some hazardsoutbreak, this system of food couldbe a milestone to poor families andtribal for their livelihood andsurviving. Besides, high potential oftherapeutic and medicinal uses canmake more popular and awareness inurban areas. As people of westerncountries are again focusing ontraditional food habits which arealready well established in rural India,hence it also has export potential inInternational market. This system offood production can generateemployment opportunities andcontribute a significant part incountry’s economy.